Corrosion of magnesium aluminate spinel-rich refractories by sulphur-containing slag. Issue 5 (May 2015) - Gehre, Patrick; Aneziris, Christos G.; Berek, Harry; Parr, Christopher; Reinmöller, Markus
Abstract Magnesium aluminate spinel-containing refractories are widely used as steel ladle linings and represent potential materials for other high temperature processes. In gasifiers, the refractories are in contact with calcium aluminosilicate-rich slags with high content of iron and sulphur. The effect of sulphur on the corrosion of spinel-rich castables has been investigated and analyzed by EDX and EBSD in SEM. In contact with coal slag at 1450 °C a spinel-rich crucible has shown areas of an initial dissolution, in which slag-surrounded micro-sized spinel grains are present. At the edge of the spinel grains, comparatively high proportions of S and Ca are detected. According to EBSD analysis no interphases are recognized. The grain size, the shape as well as the crystal quality of most of the fine spinel particles indicate rather a recrystallization after the corrosion test more than a gradual dissolution. In order to compare the obtained results, the precipitation of spinel during cooling has been reconstructed by means of thermochemical calculations using FactSage™ software.